Evaluation of antimicrobial properties of bioactive glass used in regenerative periodontal therapy - Ram Sabarish Chandrasekar; Vamsi Lavu; Kennedy Kumar; Suresh Ranga Rao (Wolters Kluwer Medknow Publications, 2015)
Context: Bone grafting materials which have an inherent anti-microbial property against initial colonizers of plaque bacteria would be useful in regenerative periodontal surgical procedures. Aims: This study was performed to analyze the antibacterial property of a Perioglas™ against a common oral commensal Streptococcus salivarius (early colonizer). Settings and Design: In vitro observational study. Materials and Methods: Perioglas™ (in various concentrations) was assessed for its antibacterial property against the ATCC 13419 strain of S. salivarius. The anti-microbial activity was analyzed in terms of reduction in colony-forming units in culture plates and smear following a 24 h incubation at 37°C. Statistical Analysis Used: Observational study - No statistical analysis applicable. Results: The bioactive glass (BAG) exerted an antibacterial effect against the S. salivarius in the suspending media and smear. The antibacterial activity of BAG increased in proportion with its concentration. Conclusions: Perioglas™ demonstrated a considerable antibacterial effect against S. salivarius at 50 mg/mL concentration.